2011
DOI: 10.1007/s10620-011-1990-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of VEGF, COX-2, and Ki-67 in Barrett’s Esophagus: Does the Length Matter?

Abstract: VEGF, COX-2, and Ki-67 were overexpressed in the majority of Barrett's samples. The length was inversely associated with VEGF expression and directly associated with Ki-67 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…COX‐2 overexpression can inhibit apoptosis and increase the proliferation and the invasiveness of cancer cells resulting in angiogenesis . Second, previous studies also found that an increased COX‐2 expression was positively associated with the development and malignant progression of Barrett's esophagus, the precursor lesion for EAC . Third, but not last, aspirin use may decrease the inflammatory complications of gastroesophageal reflux disease, the strongest risk factor for EAC .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…COX‐2 overexpression can inhibit apoptosis and increase the proliferation and the invasiveness of cancer cells resulting in angiogenesis . Second, previous studies also found that an increased COX‐2 expression was positively associated with the development and malignant progression of Barrett's esophagus, the precursor lesion for EAC . Third, but not last, aspirin use may decrease the inflammatory complications of gastroesophageal reflux disease, the strongest risk factor for EAC .…”
Section: Discussionmentioning
confidence: 98%
“…35,36 Second, previous studies also found that an increased COX-2 expression was positively associated with the development and malignant progression of Barrett's esophagus, the precursor lesion for EAC. [37][38][39][40] Third, but not last, aspirin use may decrease the inflammatory complications of gastroesophageal reflux disease, the strongest risk factor for EAC. 41 Thus, aspirin could protect against EAC by a direct and indirect multi-step process.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6]14,15 Although previous studies established a trend in the metaplasia-dysplasia-carcinoma sequence, none have clearly demonstrated whether high-grade dysplasia is significantly different from metaplasia or lowgrade dysplasia. Our study specifically demonstrates a significant and stepwise increase in microvascular density between Barrett' esophagus, low-grade dysplasia and high-grade dysplasia, which has not been previously shown.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, its levels have been found elevated in patients with intestinal type gastric cancer, lesion which is associated with IM. An increase in its levels has also been reported in patients with esophagitis and in patients with Barrett’s esophagus ( 35 , 36 ). Regarding the correlation of MetS with the VEGF, studies have shown that VEGF levels are related to MetS components.…”
Section: Discussionmentioning
confidence: 84%